Digital Leadership Kepala Sekolah dalam Manajemen Inovasi dan Peningkatan Daya Saing Lembaga Pendidikan: Systematic Literature Review - Siska Azza Rohmatillah; Laila Nurul Wahidah; Viktorius Bang (Universitas Sarjanawiyata Tamansiswa, 2026)
Digital transformation requires educational institutions not only to adopt technology but also to transform their leadership and innovation management practices. This study aims to analyze the role of school principals’ digital leadership in supporting innovation capacity and institutional competitiveness in K-12 educational institutions. The study employed a Systematic Literature Review (SLR) approach using the PRISMA protocol to examine 12 Scopus-indexed articles published between 2021-2026, which were analyzed through thematic synthesis. The findings reveal that: (1) digital leadership is multidimensional and extends beyond technical competence, with its effectiveness determined by the ability to foster an innovation-oriented culture and implement structured digital strategies; (2) the influence of school principals on school innovation is mediated by teacher commitment, collaborative culture, and knowledge management; and (3) school innovation capacity is increasingly shaped by principals’ open innovation mindset in establishing external collaborative networks. This study contributes to strengthening the innovation management perspective within educational leadership research and provides a strategic framework that can be utilized to enhance innovation and institutional competitiveness sustainably.